Pelaksanaan Kegiatan Senam Dalam Mentimulasi Perkembangan Fisik Motorik Anak di RA Annisa 2 Palangka Raya - Qotrunnada, Syarifah; Muzakki; Marifah, Siti (Yayasan Sagita Akademia Maju, 2025)
This study aims to examine the role of gymnastics in improving the physical and motor development of early childhood. Gymnastics, as a structured activity, has a significant impact on gross motor development, such as strengthening muscles, improving balance, coordination, agility, and enhancing children's kinesthetic abilities. Research shows that various types of gymnastics, such as healthy and happy gymnastics, rhythmic gymnastics, and other physical activities, are very effective in helping children develop gross motor skills. Regular gymnastics in various early childhood education institutions has been shown to improve children's abilities in jumping, running, and maintaining balance. Furthermore, gymnastics activities also support children's social and emotional development, such as building self-confidence and improving their ability to work together. The active involvement of parents and teachers is crucial for the success of gymnastics activities. Therefore, gymnastics should be an integral part of the early childhood education curriculum to support children's overall growth.